(untitled) (London, 2005)
Depleting Energy and Biorecources: The Fossil-Fuel Key, Regional Foci and Pressure Points,...
Keywords: Fossil fuels,Nguồn điện,Power resources,Nhiên liệu hóa thạch; Environmental aspects,Khía cạnh môi trường